Evaluation of the Care Safety of Patients with Surgical Interventions from a High-Complexity Institution in Medellín, Colombia (2016)
ABSTRACT: This work sought to evaluate care safety of patients with surgical interventions in the area of general surgery in terms of administrative problems in caring, incidents, and adverse events. Methods. This was an observational-type prospective descriptive study that followed up patients intervened surgically by the general surgery group of a tier IV hospital unit in the city of Medellín. Results. The study evaluated 182 patients who received complete follow up during the care process in the institution; of these, 59 (32.4%) received unsafe care (10 incidents, 9 problems with quality, and 40 adverse events); the remaining 123 (67.6%) had safe care of which, 28 developed complications in spite of not having had flaws in the care process. Regarding the health professionals responsible for patient care, we found that 57.4% of the adverse events was the responsibility of the treating physician and the remaining 42.6% was the responsibility of the nursing staff. Conclusion. The prevalence of adverse surgical events in this study was above that found in literature. Management of nursing care focused on improving the healthcare system in the area of surgery could reduce substantially not only the occurrence of flaw in caring, but also the economic burden upon the healthcare system.